2006
DOI: 10.1172/jci28941
|View full text |Cite
|
Sign up to set email alerts
|

Human CD4+ CD25hi Foxp3+ regulatory T cells are derived by rapid turnover of memory populations in vivo

Abstract: While memory T cells are maintained by continuous turnover, it is not clear how human regulatory CD4 + CD45RO + CD25 hi Foxp3 + T lymphocyte populations persist throughout life. We therefore used deuterium labeling of cycling cells in vivo to determine whether these cells could be replenished by proliferation. We found that CD4 + CD45RO + Foxp3 + CD25 hi T lymphocytes were highly proliferative, with a doubling time of 8 days, compared with memory CD4 + CD45RO + Foxp3 -CD25 -(24 days) or naive CD4 + CD45RA + Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
207
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(241 citation statements)
references
References 58 publications
(76 reference statements)
31
207
1
2
Order By: Relevance
“…Treg cells are classified into two T cells [5][6][7]. Treg cells target effector T cells and dendritic cells (DCs) by modulating their maturation and function through several mechanisms that suppress immune responses [8][9][10]; these include secretion of inhibitory cytokines (IL-10, IL-35, and TGF-β), granzyme/perforin-dependent mediated cytolysis, metabolic disruption [11][12][13][14][15], and the expression of LAG3 and CTLA4, which alter DC function [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Treg cells are classified into two T cells [5][6][7]. Treg cells target effector T cells and dendritic cells (DCs) by modulating their maturation and function through several mechanisms that suppress immune responses [8][9][10]; these include secretion of inhibitory cytokines (IL-10, IL-35, and TGF-β), granzyme/perforin-dependent mediated cytolysis, metabolic disruption [11][12][13][14][15], and the expression of LAG3 and CTLA4, which alter DC function [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…58 Furthermore, treatment with adoptive T-cell transfer can result in synergistic anti-neoplastic effects owing to the increased immunogenicity of cancer cells. 59 Yet, for all these antitumor effects, there appears to be a balance between anti-and pro-tumor effects by both CD4 þ and CD8 þ T cells, [60][61][62] and regulatory T cells can migrate into the microenvironment and suppress antitumor responses in human ovarian carcinoma. 63 Considering the variable effects of this multitude of stromal cell and immune response interactions, the mechanism by which p53 deficiency in MSCs affects T-cell function in tumors warrants further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication by Vukmanovic-Stejic and colleagues [21] demonstrated that a substantial proportion of peripheral human CD4 + CD25 high Foxp3 + Treg cells is generated from rapidly dividing, highly differentiated CD4 + memory T cells in addition to the cells of same phenotype derived from the thymus. Moreover, Liu and colleagues [34] reported that the interaction between neurons and CD4 + T cells results in the conversion of encephalogenic CD4 + T cells to CD4 + CD25 + Foxp3 + T R cells in a murine model of experimental autoimmune encephalomyelitis (EAE).…”
Section: Discussionmentioning
confidence: 99%
“…Vukmanvic-Stejic and colleagues [21] have recently reported that a proportion of peripheral CD4 + CD25 high Foxp3 + Treg cells in humans are generated from rapidly dividing memory CD4 + CD45RO + T cells in addition to thymus-derived classical CD4 + CD25 high Foxp3 + Treg cells. Furthermore, colitogenic CD4 + T cells in this colitis model proliferate and expand in response to foreign antigens more rapidly in immunodeficient SCID mice than do slow-dividing antigen-specific 'true' memory T cells [17].…”
Section: Non-colitic Lp Cd4 + T Cells Have No Characteristics Of Cd4 mentioning
confidence: 99%